Influence of various parameters on the vegetable raw material pelleting process and pellets quality (review) - S. V. Braginets; O. N. Bakhchevnikov; K. A. Deev (Аграрная наука Евро-Северо-Востока, 2023)
Determining the regularities of the process of pelleting vegetable raw materials is relevant for the improvement of technologies and technical equipment in order to reduce energy intensity and improve the quality of pellets. The generalization of the results of the research aimed at studying the influence of various parameters on the process of pelleting vegetable raw materials and the quality of feed and biofuel pellets is the purpose of the research. A selection and systematic review of the scientific literature on the subject of the study for the period of 2007-2022 has been carried out. The analysis has proved that heat pre-treatment and moistening of vegetable raw materials, as well as their composition and particle size are the factors that have the greatest impact on the quality of feed and biofuel pellets. Increasing the pressure in the range of 20...200 MPa results in increasing the pellets durability. A die temperature of around 100°C is optimum for obtaining dense pellets of highquality from vegetable raw materials. The design parameters of the pelletizer play an important role in obtaining high-quality pellets when processing vegetable raw materials. The design of the inlet in the form of a tapering cone helps to reduce energy consumption and pelleting pressure. An increase in the ratio of the die channel length to its diameter exponentially increases the pelleting pressure and its energy intensity. The interplay between the physical processes occurring in the pelletizer makes it difficult to interpret the impact of each parameter on the pelleting process, so different authors have different assessments of the contribution of individual factors in producing high-quality pellets. Therefore, the interaction between the individual pelleting parameters and their influence on the results of the process should be examined more precisely.